Pengaruh Minat Belajar terhadap Prestasi Belajar IPS pada Peserta Didik Kelas VI di SMP Yadika 2 Jakarta Barat - Utama, Wahyu; Hamid, Slamet; Sodik, Nur (FOCUS, 2023)
Describe the Effect of Learning Interest on Social Science Learning Achievement in Grade VII Students at Yadika 2 Middle School, West Jakarta. The research method used is a quantitative research method. Data collection methods are carried out using questionnaires, documentation, interviews, and observation. Then the author performs data processing which can be concluded that based on the results of research conducted by researchers at YADIKA 2 Middle School, West Jakarta, the value of t count = 1.413 is obtained. In determining the t table, this study chose ???? = 0.05 so that for ???? = 77, the value of t table = 1.665. Because the value of t count = 1.413 <t table 1.665, so based on this conclusion it can be stated that there is no effect of interest in learning (variable x) on learning achievement (variable y) Social Studies in Class VII Students at SMP Yadika 2 West Jakarta.